2020
DOI: 10.1097/qad.0000000000002663
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hospital admission for COVID-19 in HIV patients

Abstract: This study reports on hospital admission and outcomes of 69 HIV-infected individuals who were diagnosed with SARS-CoV-2 infection between February and May 2020, in a network of Italian centres. Patients’ characteristics and median days between symptoms and diagnosis were similar by hospital admission, whereas admitted patients had lower nadir CD4+ cells and current lymphocytes count. These values were also correlated to worse COVID-19 outcome. Antiretroviral drugs did not seem to be associated with disease sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 6 publications
2
28
1
Order By: Relevance
“…21 23 28 32 34 37 38 40 41 while other studies found that PLHIV with COVID-19 were more likely to have comorbidities such as diabetes and hypertension.26 29 31 35 36 …”
mentioning
confidence: 99%
“…21 23 28 32 34 37 38 40 41 while other studies found that PLHIV with COVID-19 were more likely to have comorbidities such as diabetes and hypertension.26 29 31 35 36 …”
mentioning
confidence: 99%
“…Four of these reported all-cause mortality among people diagnosed with COVID-19 [10,16,18,28] and one reported mortality due to COVID-19 as recorded on death certificates [27]. Of the remaining fourteen studies, seven made multiple comparisons between PLWH with COVID-19 and HIV-negative cohorts, and/or the general population, and/or PLWH without COVID-19, [11,12,14,15,23,25,26], two studies compared only to a HIV-negative cohort [13,19], two studies compared only cohorts of PLWH with and without COVID-19 [17,22] and three studies compared only the characteristics of PLWH with different COVID-19 disease severity [20,21,24].…”
Section: Resultsmentioning
confidence: 99%
“…We identified 1,908 records and included 19 studies in our final qualitative analysis ( Figure 1). Seventeen studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] were peer-reviewed and two were preprints [27,28]. Quality appraisal is included in Tables 1, S2 and S3.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations